Glycemic control and microvascular complications in adults with type 1 diabetes and long-lasting treated celiac disease: A case-control study. (September 2018) - Creanza, Annalisa; Lupoli, Roberta; Lembo, Erminia; Tecce, Nicola; Della Pepa, Giuseppe; Lombardi, Gianluca; Riccardi, Gabriele; Di Bonito, Procolo; Capaldo, Brunella
Highlights: GFD-treated celiac disease does not negatively impact glucose control in T1DM patients. The rate of microvascular complications was similar in patients with T1DM + GFD-treated CD compared to T1DM alone. Patients with T1DM + CD have a lower glomerular filtration rate compared to T1DM alone. Abstract: Aims: To investigate whether in type 1 diabetes (T1DM) patients the concomitance of long-lasting celiac disease (CD) treated with a gluten free diet (GFD) impacts glycaemic control and the prevalence/severity of microvascular complications. Methods: A case-control, observational study was performed in 34 patients with T1DM and GFD-treated CD and 66 patients with T1DM alone matched for age, gender, and T1DM duration. Anthropometric parameters, glucose control (HbA1c ), status of chronic complications and concomitant autoimmune diseases were evaluated. Results: HbA1c level was similar in T1DM + CD and T1DM alone (7.8 ± 1.0 vs 7.7 ± 1.1%, P = 0.57); insulin requirement was significantly higher in T1DM + CD compared with T1DM ( P = 0.04). There were no differences in systolic blood pressure while diastolic blood pressure was significantly lower in T1DM + CD ( P = 0.003). The prevalence/severity of microvascular complications was similar between the two groups. Glomerular filtration rate (eGFR) was significantly lower in T1DM + CD (100 ± 20 vs 110 ± 16 ml/min/1.73 m 2, P = 0.007). Conclusions: In patients with T1DM, the co-occurrence of long-term GFD-treated CD neither worsens glycemic control nor negatively impacts chronic microvascular complications. However, patients with T1DM + CD have lower eGFR values than those with T1DM alone.